2021
DOI: 10.1080/15623599.2021.1894632
|View full text |Cite
|
Sign up to set email alerts
|

Towards methodological adventure in cost overrun research: linking process and product

Abstract: The continued adoption of singular paradigms in the study of construction phenomena has elicited dialectical debates in scholarly literature. Calls have been made for more adventurous research methods, beyond the positivist versus interpretivist philosophical divide traditionally embraced by the industry. This study analyses the extensive scholarly debates, advancing and advocating philosophical positions to understand construction phenomena, and further narrows down the argument to within the specific domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The scholars in [62] dedicated their scientific paper to examining the methodology for forming and evaluating costs. They considered a category of costs from the standpoint of fundamental research.…”
Section: Methods Applied In the Researchmentioning
confidence: 99%
“…The scholars in [62] dedicated their scientific paper to examining the methodology for forming and evaluating costs. They considered a category of costs from the standpoint of fundamental research.…”
Section: Methods Applied In the Researchmentioning
confidence: 99%
“…This is consistent with Brunes and Lind (2014) and Subramani et al (2014) argument that cost overrun in a project could emerge from project resources becoming costlier than assessed. Aljohani et al (2017) and Amadi and Omotayo (2017) added that the high level of uncertainty involved in this type of infrastructure project potentially create flaws in the project cost estimate.…”
Section: Cost Overrun In Rail Constructionmentioning
confidence: 99%
“…Construction cost escalation has become a crucial issue in the construction industry, regardless of the size of construction projects (Eke et al , 2019; Hwang et al , 2020). Within the domain of cost overrun research, technical, risk and uncertainty-related issues have been identified as the primary front-end factors that account for cost overruns (Rahmani, 2020; Amadi, 2021). Chen et al (2019) and Hwang et al (2020) have identified different types of risks that led to cost overruns in the construction industry such as delays in the construction period (Ghauri et al 2020), changes in construction (Lou et al , 2020), misunderstanding of drawings (Rahmani, 2020) and poor communication and coordination (Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2019) and Hwang et al (2020) have identified different types of risks that led to cost overruns in the construction industry such as delays in the construction period (Ghauri et al 2020), changes in construction (Lou et al , 2020), misunderstanding of drawings (Rahmani, 2020) and poor communication and coordination (Smith, 2016). Irrational or lack of construction planning (Larsen et al , 2016; Hwang et al , 2020) causes unsystematic site management (Connaughton and Collinge, 2021), such as unbalanced allocation of labour (Amadi, 2021), leading to cost overruns. Most of these causes are related to the procurement process in construction projects and could be better managed with better procurement practices.…”
Section: Introductionmentioning
confidence: 99%